PENGENALAN NUGGET IKAN SEBAGAI INOVASI OLAHAN IKAN DI WILAYAH PESISIR KABUPATEN BUTON UTARA - Febriana Muchtar (Universitas Pahlawan Tuanku Tambusai, 2022)
Coastal areas have fishery potential that can be processed into various processed food products. Through processed innovations made from fish, the fishery potential of coastal areas can be optimally utilized. Malalanda Village is one of the villages located on the coastline of North Buton Regency. Utilization of fishery products, especially tuna and skipjack, is still limited, apart from being consumed in fresh form after going through the cooking process, skipjack is processed into smoked fish and marketed directly as a typical culinary product from North Buton Regency. Nuggets are one of the processed food products that can be made using fish known as fish nuggets. This community service aims to introduce processed fish products in the form of fish nuggets to fishing communities, especially fisherwomen and young women in Malalanda Village, Kulisusu Subdistrict, North Buton Regency. This activity was welcomed by the Village government and the Malalanda Village community. In general, the activity went smoothly and the fish nugget product was accepted and liked by the coastal community. Keywords:Coastal communities, fisheries potential, and fish nuggets